Therapeutic Potential of Butyrate for Treatment of Type 2 Diabetes - Arora, Tulika; Tremaroli, Valentina (Frontiers in Endocrinology, 2021)
Metagenomics studies have shown that type 2 diabetes (T2D) is associated with an altered gut microbiota. Whereas different microbiota patterns have been observed in independent human cohorts, reduction of butyrate-producing bacteria has consistently been found in individuals with T2D, as well as in those with prediabetes. Butyrate is produced in the large intestine by microbial fermentations, particularly of dietary fiber, and serves as primary fuel for colonocytes. It also acts as histone deacetylase inhibitor and ligand to G-protein coupled receptors, affecting cellular signaling in target cells, such as enteroendocrine cells. Therefore, butyrate has become an attractive drug target for T2D, and treatment strategies have been devised to increase its intestinal levels, for example by supplementation of butyrate-producing bacteria and dietary fiber, or through fecal microbiota transplant (FMT). In this review, we provide an overview of current literature indicating that these strategies have yielded encouraging results and short-term benefits in humans, but long-term improvements of glycemic control have not been reported so far. Further studies are required to find effective approaches to restore butyrate-producing bacteria and butyrate levels in the human gut, and to investigate their impact on glucose regulation in T2D.